“Aqueles que a sociedade julga ser de mulher, mas mulher que não estudou”: análise da relação subjetividade e trabalho de mulheres trabalhadoras domésticas diaristas - Lucena, Maria do Socorro Roberto de (2023)
Feminist perspectives that anchor their interpretations under the notions of sexual and racial division of labor, of intersectionality of social relations of sex/gender, ethnicity/race and class, have been ensuring or ensuring that these social and intersecting markers are not forgotten in the reading of the social field or the phenomena arising from it. However, they do not yet appear or are incipient in several branches of knowledge, such as Work Psychology. This scenario is especially worrying when it comes to Brazilian society, a society composed of racism, sexism and classism. In which paid domestic work (TDR) is an exponent of this story. In contemporary times, in the national territory, we are witnessing the diarization of TDR. Thus, the present thesis aimed to analyze the subjectivity-work relationship of female daily domestic workers with dimensions of sex/gender, race and class. To this end, this thesis is organized into five chapters, all in article format. The first article deals with the detailed presentation of the theoretical foundations or theoretical dialogues that supported the definition of the problem and the questions guiding the investigation. The second article brings together information about the situation of women in the context of productive restructuring and the Covid-19 pandemic. To this end, documentary research was carried out. The universe of documents consists of national and international reports, bulletins, scientific articles, among others. The panorama constructed or organized in this article adds elements and continues the theoretical discussions carried out in the previous article. Furthermore, it provides very important notes on macropolitics, the (re)formulations of inequalities that affect women's participation in the world of work and lists some current challenges in the feminist struggle. In order to narrow the discussions in relation to female domestic workers and the Brazilian reality, the third article comprises a systematic review and meta-analysis of national scientific production on the relationship between TDR and gender. The initial electronic search resulted in 1,127 productions and, after applying the inclusion criteria and excluding replicates, 16 productions were selected. With the judges' assessment, 13 articles were considered eligible for scientometric and categorical content analysis. Most of the productions analyzed point out and signal the intersectionality between sex/gender, ethnicity/race and class in the configuration of the TDR's position in the socio-occupational hierarchy, the profile of paid domestic workers and the characteristics of their working conditions and relationships. Furthermore, it was possible to identify gaps or research paths, which are relevant for the design and robustness of the empirical investigation, which make up the present work. Articles four and five refer to qualitative field research with the participation of ten women diarists, and have different analysis objectives. Unstructured interviews and a sociodemographic questionnaire were used as instruments and the hermeneutic-dialectic approach was used as the data analysis method. In both studies, the supporting theoretical references were the Sociology of the Sexual Division of Labor, the Afrocentric paradigm of gender discussions and the Psychodynamics of Work. The objective of the fourth article was to understand the repercussions of sex/gender, race and class in everyday work and the subjective mobilization of female workers. We highlight that suspicion at work, work overload and the frantic pace of carrying out the activity, the threat or occurrence of sexual harassment are some of the situations detected in the daily lives of day laborers and which are engendered in the insignia, relationships and material conditions arising from differentiations/hierarchies of race, sex/gender and class. Furthermore, we identified among day laborers processes of naturalization or assimilation of these differentiations/hierarchizations that have repercussions on their individual and collective conduct, although movements of resistance or inflection were also observed. The objective of the fifth article was to analyze the impacts of the pandemic context on the work activity and mental health of female daily domestic workers, taking into account the intersectionality between sex/gender, race and class at work. The findings reflect the role of sex/gender, race and class inequalities in worsening the working/living conditions of women day laborers and the negative consequences on their health. The pandemic experiences of these workers are marked by extreme subsistence difficulties, new dilemmas or risks and the updating of micro-oppressions in labor relations, which give rise to various discomforts for them, from anxiety to feelings of inferiority. The combination of articles provides elements of intelligibility about the condition of female daily domestic workers and their relationship with the configuration of subjective experiences and the quality of health of research participants. Furthermore, it invites us to reflect critically and inventively on the difficulties or ways of confronting sex/gender, race and class disparities, which substantially permeate the work/life issues of day laborers.